APLICAÇÃO DO PREPARADO HOMEOPÃTICO Carbo vegetabilis E DESENVOLVIMENTO DO MORANGUEIRO - Rossi, Fabricio; Melo, Paulo César Tavares; Ambrosano, Edmilson José; Guirado, Nivaldo (REVISTA DE AGRICULTURA, 2015)
APLICAÇÃO DO PREPARADO HOMEOPÃTICO Carbo vegetabilis E DESENVOLVIMENTO DO MORANGUEIRO